2018
DOI: 10.1007/s00464-018-6100-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic evaluation of sentinel lymph node biopsy using indocyanine green and infrared or fluorescent imaging in gastric cancer: a systematic review and meta-analysis

Abstract: We found encouraging results regarding the accuracy, diagnostic odds ratio, and specificity of the test. The sensitivity was not optimal but may be improved by a strict protocol to augment the technique. Given the number and heterogeneity of studies, our results must be viewed with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Unfortunately, the individual lymphatic pattern is visually indistinguishable. In recent years, several strategies have been investigated aimed at intraoperatively visualizing the single-patient lymphatics' anatomy for surgical guidance, with ICG fluorescence emerging as the preferred method in many fields of cancer surgery [19,20,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the individual lymphatic pattern is visually indistinguishable. In recent years, several strategies have been investigated aimed at intraoperatively visualizing the single-patient lymphatics' anatomy for surgical guidance, with ICG fluorescence emerging as the preferred method in many fields of cancer surgery [19,20,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Skubleny et al recently published a meta-analysis of sentinel lymph node biopsy using indocyanine green and infrared or fluorescent imaging of gastric cancer. 46 The sensitivity of this meta-analysis was relatively low as 87% (0.80~0.93) in pooled analysis. The study also reported sensitivity of the studies using infrared electronic endoscopic as 97% and that of the studies using NIR fluorescent imaging systems as 72%.…”
Section: Future Of Node Navigation Using Nir Imagingmentioning
confidence: 67%
“…Multiple studies have evaluated the safety and feasibility for sentinel node mapping in gastric cancer surgery [9,12]. The use of dual-tracer methods was found to be the most reliable to identify sentinel lymph nodes in gastric cancer [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…If the absence of lymph node metastasis could be established by using a sentinel lymph node procedure, an unnecessary gastrectomy may be avoided. A recent meta-analysis concluded that sentinel node mapping with the use of indocyanine green (ICG) fluorescence imaging in gastric cancer is feasible with encouraging results in terms of detection rate, accuracy and sensitivity [9]. Most of the available literature studies are from Asia and make use of conventional laparoscopic techniques.…”
Section: Introductionmentioning
confidence: 99%